ANALISIS EFEKTIVITAS IKLAN INTERNET PRODUK SHAMPOO PANTENE DENGAN MENGGUNAKAN METODE EPIC MODEL DAN PENGARUHNYA TERHADAP CITRA MEREK (Studi Empiris pada Masyarakat Kota Pontianak) - B11110067, WILSON HARTANTO (Jurnal Manajemen Update, 2014)
Advertising is one important strategy in developing the business, including in developing the brand image of the product being advertised. This research aims to analyze the effectiveness of internet advertising on Pantene shampoo using EPIC Model method which consists of Empathy, Persuasion, Impact, and Communication also measure its influence on brand image. This research was designed as an associative/causal research. The sampling technique used is purposive sampling with a sample size of 100 respondents in the city of Pontianak. The analysis technique used is multiple linear regression analysis using SPSS version 20.0. The results of the analysis of the data obtained shows that Pantene shampooadvertisement that aired on internet sites is quite effectiveas indicated by thevalueofEPICrate at 3.34. The processing of the data showed that Empathy, Persuasion, Impact and Communication had a significant effect on Pantene shampoo brand image with a significance value of 0.000 and R2 value of 58.2%, while the remaining 41.8% are other factors that were not examined in this research. Partially, the influence ofEmpathyandImpactonPanteneshampoobrand imageisnot significantandpositive, meanwhile the influenceofPersuasionandCommunicationon Pantene shampoobrandimage issignificantandpositive. Keywords : EPIC Model and brand image